Performance of Basic Life Support by Lifeboat Crewmembers While Wearing a Survival Suit and Life Vest: A Randomized Controlled Trial - Allart M. Venema; Marko M. Sahinovic; Albert J. D. W. R. Ramaker; Yvette N. van de Riet; Anthony R. Absalom; J. K. Götz Wietasch (Frontiers Media S.A., 2021)
Introduction: Crewmembers of the "Royal Netherlands Sea Rescue Institution" (KNRM) lifeboats must wear heavy survival suits with integrated lifejackets. This and the challenging environment onboard (boat movements, limited space) might influence Basic Life Support (BLS) performance. The primary objective of this study was to assess the impact of the protective gear on single-rescuer BLS-quality.Material and Methods: Sixty-five active KNRM crewmembers who had recently undergone a BLS-refresher course were randomized to wear either their protective gear (n = 32) or their civilian clothes (n = 33; control group) and performed five 2-min sessions of single rescuer BLS on a mannequin on dry land. BLS-quality was assessed according to Dutch and European Resuscitation guidelines. A between group analysis (Mann-Whitney U) and a repeated within group analysis of both groups (Friedman test) were performed.Results: There were no major demographic differences between the groups. The protective gear did not significant impair BLS-quality. It was also not associated with a significant increase in the perceived exertion of BLS (Borg's Rating scale). Compression depth, compression frequency, the percentage of correct compression depth and of not leaning on the thorax, and ventilation volumes in both groups were suboptimal when evaluated according to the BLS-guidelines.Conclusions: The protective gear worn by KNRM lifeboat-crewmembers does not have a significant influence on BLS-quality under controlled study conditions. The impact and significance on outcome in real life situations needs to be studied further. This study provides valuable input for optimizing the BLS-skills of lifeboat crewmembers.